Preparation method of lithium vanadium phosphate positive electrode slurry, preparation method of positive electrode plate and battery

By adding and stirring binder, conductive agent, conductive carbon and lithium vanadium phosphate in steps, the problem of difficulty in adjusting the viscosity of the lithium vanadium phosphate positive electrode slurry is solved, and uniform coating of the electrode sheet and good electrochemical performance of the battery are achieved.

CN119750527APending Publication Date: 2025-04-04PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411861090.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art lacks a preparation method for lithium vanadium phosphate positive electrode slurry, which makes it difficult to adjust its viscosity and affects the coating and electrochemical properties of the electrode sheet.

Method used

The viscosity of the slurry is adjusted by adding binder, conductive agent, conductive carbon and lithium vanadium phosphate in steps and stirring under vacuum to form a suitable positive electrode slurry.

Benefits of technology

The uniform dispersion of the positive electrode slurry is achieved, the surface of the electrode sheet is smooth and free of cracks, and the light is not leaked after rolling, and the battery has good electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005193218720000011
    Figure HDA0005193218720000011
  • Figure HDA0005193218720000012
    Figure HDA0005193218720000012
  • Figure HDA0005193218720000013
    Figure HDA0005193218720000013
Patent Text Reader

Abstract

The invention provides a lithium vanadium phosphate positive electrode slurry preparation method, which comprises: S1) adding a conductive agent solution to a binder solution, and stirring to obtain a first intermediate slurry; s2) mixing the first intermediate slurry with conductive carbon to obtain second intermediate slurry; and S3) mixing the second intermediate slurry with lithium vanadium phosphate to obtain third intermediate slurry, and adjusting the viscosity of the third intermediate slurry to obtain the lithium vanadium phosphate positive electrode slurry. The invention also provides a preparation method of the positive pole piece and a battery. The lithium vanadium phosphate positive electrode slurry is prepared by adopting the step-by-step means, and the viscosity and the solid content of the positive electrode slurry are adjusted, so that the uniform dispersion of the positive electrode slurry is ensured; on the basis, the surface of a positive pole piece prepared from the positive pole slurry is smooth and crack-free, and light leakage is avoided after the positive pole piece is folded after rolling, so that the electrochemical performance of the total battery is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a method for preparing a lithium vanadium phosphate positive electrode slurry, a method for preparing a positive electrode sheet, and a battery. Background Art

[0002] The positive electrode material is the core part of the lithium battery and plays a decisive role in the performance and application of the battery. Among the many positive electrode materials, lithium iron phosphate is the mainstream development trend of lithium battery positive electrode materials due to its low cost and stable electrochemical performance. However, lithium iron phosphate has poor low-temperature performance, and its capacity decay is serious below 0°C, especially below -20°C. It is difficult to use in special environments, which greatly limits its development. Lithium vanadium phosphate and lithium iron phosphate belong to the phosphate-based positive electrode materials, which have the advantages of high theoretical capacity, good safety performance, and high discharge voltage; in addition, lithium vanadium phosphate also has the significant advantage of excellent low-temperature performance. Therefore, lithium vanadium phosphate can be used as an ideal substitute for lithium iron phosphate, and can be used in high-altitude and cold areas such as plateaus, deep seas, and polar regions, as well as extremely cold areas such as high altitudes and space.

[0003] However, existing patents are mainly focused on the preparation of lithium vanadium phosphate materials and the improvement of electrochemical performance. There is a lack of relevant patents in the preparation of lithium vanadium phosphate positive electrode slurry, which greatly affects the commercial application of lithium vanadium phosphate materials. In addition, although lithium iron phosphate and lithium vanadium phosphate are both phosphate-based positive electrode materials, there are obvious differences in their coating performance. Lithium vanadium phosphate with a similar particle size to lithium iron phosphate requires a greater amount of binder when slurrying, which increases the viscosity of lithium vanadium phosphate slurry. It is necessary to form a solid content ratio suitable for lithium vanadium phosphate material coating slurry during the process of adding NMP to adjust the viscosity. The change in binder content and the adjustment of the final viscosity parameters put forward new requirements for slurry homogenization and coating, and the adjusted slurry solid content parameters also put forward new requirements for the subsequent preparation system of the pole piece. Therefore, it is impossible to directly use the slurry preparation process of lithium iron phosphate, and it is necessary to form a preparation method for lithium vanadium phosphate material slurry. Summary of the invention

[0004] The technical problem solved by the present invention is to provide a method for preparing lithium vanadium phosphate positive electrode slurry. The positive electrode slurry prepared in the present application is used to coat the positive electrode plate, which can make the surface of the plate smooth and free of cracks, and no light leakage when folded after rolling, and the prepared battery has good electrochemical performance.

[0005] In view of this, the present application provides a method for preparing a lithium vanadium phosphate positive electrode slurry, comprising the following steps:

[0006] S1) adding a conductive agent solution to a binder solution, and stirring to obtain a first intermediate slurry;

[0007] S2) mixing the first intermediate slurry and conductive carbon to obtain a second intermediate slurry;

[0008] S3) mixing the second intermediate slurry and lithium vanadium phosphate to obtain a third intermediate slurry, and adjusting the viscosity of the third intermediate slurry to obtain a lithium vanadium phosphate positive electrode slurry.

[0009] Preferably, in step S1), the method for preparing the binder solution is specifically as follows:

[0010] Mixing polyvinylidene fluoride and N-methylpyrrolidone, and stirring to obtain a binder solution;

[0011] The content of polyvinylidene fluoride in the binder solution is 3.5-4.5wt%;

[0012] The stirring is first performed at a revolution speed of 30 to 40 rpm and an autorotation speed of 1500 to 2000 rpm for 30 to 40 min, and then stirred at a revolution speed of 30 to 40 rpm and an autorotation speed of 4000 to 5000 rpm for 4 to 8 h under vacuum conditions;

[0013] The preparation method of the conductive agent solution is specifically as follows:

[0014] Adding graphene and / or carbon nanotubes into N-methylpyrrolidone and subjecting to ultrasonic treatment to obtain a conductive agent solution;

[0015] The content of N-methylpyrrolidone in the conductive agent solution is 95-96 wt %.

[0016] Preferably, in step S1), the stirring is performed at a revolution speed of 30 to 40 rpm and a rotation speed of 4000 to 5000 rpm for 30 to 40 min.

[0017] Preferably, in step S2), the conductive carbon includes one of acetylene black, SuperP and Ketjen black, and the mixing is carried out in a stirring manner, and the stirring is specifically carried out in a manner of stirring at a revolution speed of 30 to 40 rpm and a rotation speed of 4000 to 5000 rpm for 30 to 40 minutes.

[0018] Preferably, in step S3), the particle size of the lithium vanadium phosphate is 0.5-6 μm; the mixing is performed by stirring, and the stirring is specifically performed by stirring at a revolution speed of 30-40 rpm and a rotation speed of 4000-5000 rpm for 30-40 min.

[0019] Preferably, in step S3), the viscosity adjusting agent is N-methylpyrrolidone, the viscosity is 8000-12000 mapa.s, and the solid content is 40-60%.

[0020] Preferably, the mass ratio of the binder, the conductive agent, the conductive carbon and the lithium vanadium phosphate is (4.0-5.0): (0.8-1.0): (1.2-1.5): (92.5-94).

[0021] The present application also provides a method for preparing a positive electrode sheet, comprising:

[0022] The positive electrode slurry is formed on the surface of the current collector, and then rolled and pressed to obtain a positive electrode sheet;

[0023] The positive electrode slurry is the positive electrode slurry prepared by the preparation method.

[0024] Preferably, the drying is first performed at 60-80°C and then at 100-120°C; the compaction density of the positive electrode sheet is 2.0-2.1 g / cm 3 .

[0025] The present application also provides a battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that the positive electrode sheet is a positive electrode sheet prepared by the preparation method.

[0026] The present application provides a method for preparing a lithium vanadium phosphate positive electrode slurry, which comprises first adding a conductive agent solution to a binder solution, stirring to obtain a first intermediate slurry, then mixing the first intermediate slurry with conductive carbon to obtain a second intermediate slurry, then mixing the second intermediate slurry with lithium vanadium phosphate to obtain a third intermediate slurry, and finally adjusting the viscosity of the third intermediate slurry to obtain a lithium vanadium phosphate positive electrode slurry; in the preparation process of the positive electrode slurry, the conductive agent solution is added to the binder solution to ensure the dispersion of the binder and the uniform dispersion of the conductive agent, and the conductive carbon is added to the system before the lithium vanadium phosphate to ensure the dispersion effect of the conductive carbon to avoid agglomeration of the conductive carbon and the lithium vanadium phosphate. Therefore, the present application adopts the above-mentioned step-by-step method to prepare the lithium vanadium phosphate positive electrode slurry to ensure the uniform dispersion of the positive electrode slurry; on this basis, the surface of the positive electrode sheet prepared by the positive electrode slurry is smooth and free of cracks, and does not leak light when folded in half after rolling, so that the electrochemical performance of the whole battery is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The following are photos of the coating and rolling of the pole pieces with different proportions of the binder added to them;

[0028] Figure 2 The following are the photos of the electrode after direct drying at 120°C (left picture) and the electrode after step-by-step drying (right picture);

[0029] Figure 3 The charge and discharge curve diagram and cycle performance diagram of the lithium vanadium phosphate soft-pack full battery prepared in Example 1 of the present invention;

[0030] Figure 4 This is a physical photo of the electrode sheet after coating with the positive electrode slurry prepared in Comparative Example 1 of the present invention;

[0031] Figure 5 This is a photo of the electrode after coating with the positive electrode slurry prepared in Example 1 of the present invention;

[0032] Figure 6 This is a photo of the electrode sheet after rolling of the positive electrode slurry prepared in Example 1 of the present invention;

[0033] Figure 7 The room temperature 2C cycle performance graph (left figure) and the 0°C cycle performance curve graph (right figure) of the full battery prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0035] In view of the problem in the prior art that the viscosity of lithium vanadium phosphate slurry needs to be readjusted to ensure the performance of the positive electrode sheet, the present application provides a method for preparing lithium vanadium phosphate positive electrode slurry and a method for preparing a positive electrode sheet; in the process of preparing lithium vanadium phosphate positive electrode slurry, the present application adds various raw materials in steps and preferably adjusts the proportion of the raw materials so that the conductive carbon can be evenly dispersed in the slurry and the coating effect is guaranteed; in the process of preparing the positive electrode sheet, the uniform dispersion of the raw materials in the positive electrode slurry is beneficial to the uniformity of the surface of the positive electrode sheet, and the step-by-step drying method is preferably used to avoid cracking and falling off of the electrode sheet. Specifically, an embodiment of the present invention discloses a method for preparing lithium vanadium phosphate positive electrode slurry, comprising the following steps:

[0036] S1) adding a conductive agent solution to a binder solution, and stirring to obtain a first intermediate slurry;

[0037] S2) mixing the first intermediate slurry and conductive carbon to obtain a second intermediate slurry;

[0038] S3) mixing the second intermediate slurry and lithium vanadium phosphate to obtain a third intermediate slurry, and adjusting the viscosity of the third intermediate slurry to obtain a lithium vanadium phosphate positive electrode slurry.

[0039] In the preparation process of lithium vanadium phosphate positive electrode slurry, the present application first adds a conductive agent solution to a binder solution, and obtains a first intermediate slurry after stirring; in this process, it is preferred to prepare a binder solution and a conductive agent solution separately, and specifically, the preparation method of the binder solution includes:

[0040] Mix polyvinylidene fluoride and N-methylpyrrolidone, use a double planetary mixer, stir at a revolution speed of 30-40 rpm and a rotation speed of 1500-2000 rpm for 30-40 minutes, open the tank body to scrape the wall material into the slurry, and then stir at a revolution speed of 30-40 rpm and a rotation speed of 4000-5000 rpm for 4-8 hours under vacuum conditions.

[0041] According to the above preparation method, the binder in the binder solution is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone; the content of polyvinylidene fluoride in the binder solution is 3.5-4.5wt%, specifically, the content of polyvinylidene fluoride in the binder solution is 3.8-4.2wt%, more specifically, the content of polyvinylidene fluoride in the binder solution is 4wt%.

[0042] The preparation method of the conductive agent solution is specifically as follows:

[0043] The conductive agent is added to the organic solvent N-methylpyrrolidone and ultrasonicated for 2 to 8 hours.

[0044] The conductive agent is selected from one or both of graphene and carbon nanotubes, and specifically, the conductive agent is selected from graphene or carbon nanotubes. The content of the conductive agent in the conductive agent solution is 4.0-5.0wt%, specifically, the content of the conductive agent in the conductive agent solution is 4.2-4.8wt%, and more specifically, the content of the conductive agent in the conductive agent solution is 4.5wt%.

[0045] After the preparation of the binder solution and the conductive agent solution, the conductive agent solution is added to the binder solution, and the first intermediate slurry is obtained after stirring; the stirring is carried out by a double planetary mixer, and the stirring is carried out for 30 to 40 minutes at a revolution of 30 to 40 rpm and a rotation speed of 4000 to 5000 rpm. In the present application, the binder is a polymer material, which is difficult to disperse and takes a long time, so the binder solution needs to be prepared in advance; the conductive agent graphene and carbon nanotubes in the conductive agent solution have a large specific surface area, are easy to agglomerate together, and are not easy to disperse, so the conductive agent solution needs to be prepared in advance.

[0046] The present application then mixes the first intermediate slurry obtained above with conductive carbon to obtain a second intermediate slurry; in this process, the conductive carbon is selected from one of acetylene black, SuperP and Ketjen black, and the mixing is carried out in a stirring manner, and the stirring is specifically stirred for 30 to 40 minutes at a revolution speed of 30 to 40 rpm and a rotation speed of 4000 to 5000 rpm. The conductive carbon is added in a small amount, has a small particle size and a large specific surface area, and is easy to agglomerate. In order to ensure the dispersion effect, it needs to be added before lithium vanadium phosphate.

[0047] According to the present invention, the second intermediate slurry and lithium vanadium phosphate are then mixed to obtain a third intermediate slurry; in this process, the particle size of the lithium vanadium phosphate is 0.5-6 μm, specifically, the particle size of the lithium vanadium phosphate is 1-5 μm, and more specifically, the particle size of the lithium vanadium phosphate is 2-4 μm. The mixing is carried out in a stirring manner, specifically using a double planetary mixer, stirring for 30-40 minutes at a revolution speed of 30-40 rpm and a rotation speed of 4000-5000 rpm.

[0048] The above-mentioned binder, conductive agent, conductive carbon and lithium vanadium phosphate are added step by step to avoid agglomeration of conductive carbon and lithium vanadium phosphate, ensure the dispersibility of conductive carbon, make the above-mentioned raw materials dispersed evenly in the positive electrode slurry, and ensure the conductivity of the positive electrode sheet.

[0049] The present application finally adjusts the viscosity of the third intermediate slurry to obtain lithium vanadium phosphate positive electrode slurry; specifically, the viscosity adjusting agent is selected from N-methylpyrrolidone, the viscosity is adjusted to 8000-12000mapa.s, and the solid content is 40-60%; specifically, the viscosity is adjusted to 9000-11000mapa.s, and the solid content is 45-55%; more specifically, the viscosity is adjusted to 9500-10000mapa.s, and the solid content is 48-52%. In the present application, the third intermediate slurry is adjusted to the above viscosity to increase the fluidity of the slurry, facilitate leveling, and avoid the problem of cracking during the drying process and insufficient surface density of the pole piece caused by too low solid content.

[0050] In the lithium vanadium phosphate positive electrode slurry prepared in the present application, the total mass percentage of the binder, the conductive agent, the conductive carbon and the lithium vanadium phosphate is 100%, and the mass ratio is (4.0-5.0): (0.8-1.0): (1.2-1.5): (92.5-94); specifically, the mass ratio of the binder, the conductive agent, the conductive carbon and the lithium vanadium phosphate is (4.5-4.8): (0.8-1.0): (1.3-1.4): (92.8-93.7); in a specific embodiment, the mass ratio of the binder, the conductive agent, the conductive carbon and the lithium vanadium phosphate is 5:0.8:1.2:93 or 5.0:1.0:1.2:92.8. The binder has a significant effect on the adhesion of the positive electrode slurry on the electrode. If the ratio is too low, the adhesion is poor and the powder is easy to fall off. If the ratio is too high, the electrode becomes more brittle and easy to break. The preferred ratio is 5.0. The results are as follows. Figure 1As shown. Conductive agent and conductive carbon are used to improve the conductivity of active materials. Conductive carbon has better conductivity, but it is difficult to mix. A small amount of addition improves the conductivity of the material. The overall amount of conductive agent and conductive carbon added should not be too much. It is necessary to increase the proportion of active material lithium vanadium phosphate to ensure the energy density of the battery; N-methylpyrrolidone is added to adjust the viscosity of the slurry. If too little is added, the viscosity is too high, which is not conducive to leveling and coating. If too much is added, the solid content is too low, and the pole piece is easy to crack and fall off during the drying process.

[0051] The present application also provides a method for preparing a positive electrode sheet, comprising:

[0052] The positive electrode slurry is formed on the surface of the current collector, and then rolled and pressed to obtain a positive electrode sheet;

[0053] The positive electrode slurry is the positive electrode slurry described in the above scheme.

[0054] In the process of preparing the positive electrode sheet, the current collector can be selected from aluminum foil; the method is a method well known to those skilled in the art, and a coating method can be used. The drying can be first dried at 60-80°C and then dried at 100-120°C; more specifically, the drying can be first dried at 80°C to remove N-methylpyrrolidone, and then dried at 120°C to avoid cracking of the electrode sheet caused by direct high-temperature baking; Figure 2 As shown, Figure 2 The left picture shows a real photo of the electrode directly dried at 120℃, and the right picture shows a real photo of the electrode first dried at 80℃ and then dried at 120℃. It can be seen from the pictures that direct drying of the electrode will cause cracking problems.

[0055] In this application, the compaction density of the positive electrode sheet is 2.0-2.1 g / cm 3 .

[0056] The present application also provides a battery, comprising a positive electrode plate, a negative electrode plate and an electrolyte, wherein the positive electrode plate is a positive electrode plate prepared by the preparation method described in the above scheme.

[0057] In view of the processing characteristics of lithium vanadium phosphate materials, the present application provides a method for preparing lithium vanadium phosphate positive electrode slurry, forming a slurry preparation and coating process suitable for lithium vanadium phosphate materials. The surface of the pole piece obtained by this method is smooth and free of cracks, and it does not leak light when folded after rolling. The full battery assembled with the pole piece has good electrochemical performance, meets the needs of battery assembly, and provides certain technical support for the commercial application of lithium vanadium phosphate.

[0058] In order to further understand the present invention, the preparation method of the lithium vanadium phosphate positive electrode slurry and the preparation method of the positive electrode sheet provided by the present invention are described in detail below in combination with the embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0059] Example 1

[0060] A certain amount of PVDF and NMP were weighed and added into a double planetary mixer, the mass fraction of PVDF was 4%, and stirred for 30 min at a revolution of 30 rpm and a rotation speed of 1500 rpm. The tank was opened to scrape the wall material into the slurry, and then stirred for 4 h at a revolution of 30 rpm and a rotation speed of 4000 rpm under vacuum conditions to obtain a binder solution S1;

[0061] Weigh a certain amount of carbon nanotubes and NMP into a beaker, the mass fraction of carbon nanotubes is 4.5%, and perform ultrasonic treatment for 2 hours to obtain a carbon nanotube conductive agent solution S2;

[0062] S2 was added to S1, and stirred at an orbital speed of 30 rpm and an autorotation speed of 4000 rpm for 30 min to obtain an intermediate slurry S3; SuperP was added to S3, and stirred at an orbital speed of 30 mp and an autorotation speed of 4000 rpm for 30 min to obtain an intermediate slurry S4; active material lithium vanadium phosphate was added to S4, and stirred at an orbital speed of 30 rpm and an autorotation speed of 4000 rpm for 30 min to obtain an intermediate slurry S5, wherein the mass ratio of PVDF: carbon nanotube (CNT): SuperP: lithium vanadium phosphate = 5.0%: 0.8%: 1.2%: 93%; an appropriate amount of NMP was added to adjust the viscosity of S5 to 12000 mapa.s to obtain the desired positive electrode slurry;

[0063] The slurry was coated on aluminum foil, and the electrode was pre-baked at 80°C under vacuum conditions, and then dried at 120°C; the electrode was rolled and the compaction density was controlled at 2.0g / cm 3 , and obtain the electrode piece that can be used to assemble the battery.

[0064] Use commercial lithium iron phosphate battery electrolyte and negative electrode to assemble lithium vanadium phosphate full battery and test electrochemical performance; Figure 3 (a) is the charge and discharge curve of the lithium vanadium phosphate soft-pack full battery at 0.1C and 2.8-4.3V. The design capacity is 1.8Ah, and the 0.1C discharge capacity is 1.74Ah, reaching 96.7% of the design capacity; Figure (b) is the cycle performance diagram of the lithium vanadium phosphate full battery at 2C rate. Its first discharge capacity is 1.68Ah, and the discharge capacity is 1.60Ah after 200 cycles. The capacity retention rate is 95.2%, showing a good capacity retention rate.

[0065] Example 2

[0066] A certain amount of PVDF and NMP were weighed and added into a double planetary mixer, the mass fraction of PVDF was 4%, and stirred for 30 min at a revolution of 30 rpm and a rotation speed of 1500 rpm. The tank was opened to scrape the wall material into the slurry, and then stirred for 4 h at a revolution of 30 rpm and a rotation speed of 4000 rpm under vacuum conditions to obtain a binder solution S1;

[0067] Weigh a certain amount of carbon nanotubes and NMP and add them to a beaker, the mass fraction of carbon nanotubes is 4.0%, and ultrasonicate for 2 hours to obtain a carbon nanotube conductive agent solution S2; add S2 to S1, stir at a revolution of 30 rmp and a rotation speed of 4000 rmp for 30 min to obtain an intermediate slurry S3; add acetylene black to S3, stir at a revolution of 30 rmp and a rotation speed of 4000 rmp for 30 min to obtain an intermediate slurry S4; add active material lithium vanadium phosphate to S4, stir at a revolution of 30 rmp and a rotation speed of 4000 rmp for 30 min to obtain an intermediate slurry S5, wherein the mass ratio of PVDF: carbon nanotubes (CNT): acetylene black: lithium vanadium phosphate = 5.0%: 0.8%: 1.2%: 93%; add an appropriate amount of NMP to adjust the viscosity of S5 to 9000 mapa.s to obtain the desired positive electrode slurry;

[0068] The slurry was coated on aluminum foil, and the electrode was pre-baked at 80°C under vacuum conditions, and then dried at 120°C; the electrode was rolled and the compaction density was controlled at 2.0g / cm 3 , and obtain the pole piece that can be used to assemble the battery; use the commercial lithium iron phosphate battery electrolyte and negative pole piece to assemble the lithium vanadium phosphate full battery, and test the electrochemical performance. The results show that the lithium vanadium phosphate soft-pack full battery prepared in this example has a charge and discharge curve of 0.1C and 2.8-4.3V, and a 0.1C discharge capacity of 1.72Ah.

[0069] Example 3

[0070] A certain amount of PVDF and NMP were weighed and added into a double planetary mixer, the mass fraction of PVDF was 4%, and stirred for 40 min at a revolution of 40 rpm and a rotation speed of 2000 rpm. The tank was opened to scrape the wall material into the slurry, and then stirred for 4 h at a revolution of 40 rpm and a rotation speed of 5000 rpm under vacuum conditions to obtain a binder solution S1;

[0071] Weigh a certain amount of graphene and NMP and add them to a beaker, the mass fraction of graphene is 4.5%, and ultrasonicate for 2 hours to obtain a graphene conductive agent solution S2; add S2 to S1, stir at a revolution of 40rmp and a rotation speed of 5000rmp for 40min to obtain an intermediate slurry S3; add SuperP to S3, stir at a revolution of 40rmp and a rotation speed of 5000rmp for 40min to obtain an intermediate slurry S4; add active material lithium vanadium phosphate to S4, stir at a revolution of 40rmp and a rotation speed of 5000rmp for 40min to obtain an intermediate slurry S5, wherein the mass ratio of PVDF: graphene: SuperP: lithium vanadium phosphate = 5.0%: 1.0%: 1.2%: 92.8%; add an appropriate amount of NMP to adjust the viscosity of S5 to 12000mapa.s to obtain the desired positive electrode slurry;

[0072] The slurry was coated on aluminum foil, and the electrode was pre-baked at 80°C under vacuum conditions, and then dried at 120°C; the electrode was rolled and the compaction density was controlled at 2.0g / cm 3 , and obtain the pole piece that can be used to assemble the battery; the commercial lithium iron phosphate battery electrolyte and negative pole piece are used to assemble the lithium vanadium phosphate full battery, and the electrochemical performance is tested. The results show that the charge and discharge curve of the lithium vanadium phosphate soft pack full battery at 0.1C and 2.8-4.3V, and the 0.1C discharge capacity is 1.77Ah.

[0073] Comparative Example 1

[0074] The amount of raw materials added is the same as that in Example 1, except that all raw materials are directly stirred and mixed to obtain positive electrode slurry;

[0075] The slurry was coated on aluminum foil, and the electrode was pre-baked at 80°C under vacuum conditions, and then dried at 120°C; the electrode was then rolled and the compaction density was controlled at 2.2g / cm 3 , and obtain the electrode piece that can be used to assemble the battery.

[0076] Figure 4 This is a real photo of the pole piece prepared in this comparative example. It can be seen from the figure that obvious agglomerated particles appear on the surface of the pole piece prepared in this comparative example.

[0077] Figure 5 This is a photo of the positive electrode slurry prepared in Example 1 coated with aluminum foil and the electrode piece after drying. It can be seen from the figure that the surface of the electrode piece prepared in Comparative Example 1 is smooth; Figure 6 This is a photo of the pole piece prepared in Example 1 after rolling. Figure 6 It can be seen that there is no crack in the electrode after rolling. The lithium vanadium phosphate Ah-level full battery prepared in Example 1 has a discharge capacity of 1.4923Ah after 300 cycles at 2C rate at room temperature, and a capacity retention rate of 88.9%; the discharge capacity is 0.94Ah after 250 cycles at 2C rate at 0°C, and the capacity retention rate is 88.3%. Figure 7 shown.

[0078] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0079] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a lithium vanadium phosphate positive electrode slurry, comprising the following steps: S1) adding a conductive agent solution to a binder solution, and stirring to obtain a first intermediate slurry; S2) mixing the first intermediate slurry and conductive carbon to obtain a second intermediate slurry; S3) mixing the second intermediate slurry and lithium vanadium phosphate to obtain a third intermediate slurry, and adjusting the viscosity of the third intermediate slurry to obtain a lithium vanadium phosphate positive electrode slurry.

2. The preparation method according to claim 1, characterized in that: In step S1), the preparation method of the binder solution is specifically as follows: Mixing polyvinylidene fluoride and N-methylpyrrolidone, and stirring to obtain a binder solution; The content of polyvinylidene fluoride in the binder solution is 3.5-4.5wt%; The stirring is first performed at a revolution speed of 30 to 40 rpm and an autorotation speed of 1500 to 2000 rpm for 30 to 40 min, and then stirred at a revolution speed of 30 to 40 rpm and an autorotation speed of 4000 to 5000 rpm for 4 to 8 h under vacuum conditions; The preparation method of the conductive agent solution is specifically as follows: Adding graphene and / or carbon nanotubes into N-methylpyrrolidone and subjecting to ultrasonic treatment to obtain a conductive agent solution; The content of N-methylpyrrolidone in the conductive agent solution is 95-96 wt %.

3. The preparation method according to claim 1, characterized in that: In step S1), the stirring is specifically carried out at a revolution speed of 30 to 40 rpm and a rotation speed of 4000 to 5000 rpm for 30 to 40 minutes.

4. The preparation method according to claim 1, characterized in that: In step S2), the conductive carbon includes one of acetylene black, SuperP and Ketjen black, and the mixing is carried out in a stirring manner. The stirring is specifically carried out in a manner of stirring at a revolution speed of 30 to 40 rpm and a rotation speed of 4000 to 5000 rpm for 30 to 40 minutes.

5. The preparation method according to claim 1, characterized in that: In step S3), the particle size of the lithium vanadium phosphate is 0.5-6 μm; the mixing is performed by stirring, and the stirring is specifically performed by stirring at a revolution speed of 30-40 rpm and a rotation speed of 4000-5000 rpm for 30-40 min.

6. The preparation method according to claim 1, characterized in that: In step S3), the viscosity adjusting agent is N-methylpyrrolidone, the viscosity is 8000-12000 mapa.s, and the solid content is 40-60%.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the binder, the conductive agent, the conductive carbon and the lithium vanadium phosphate is (4.0-5.0): (0.8-1.0): (1.2-1.5): (92.5-94).

8. A method for preparing a positive electrode sheet, comprising: The positive electrode slurry is formed on the surface of the current collector, and then rolled and pressed to obtain a positive electrode sheet; The positive electrode slurry is the positive electrode slurry prepared by the preparation method according to any one of claims 1 to 7.

9. The preparation method according to claim 8, characterized in that: The drying is first performed at 60-80°C and then at 100-120°C; the compaction density of the positive electrode sheet is 2.0-2.1 g / cm 3 .

10. A battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The positive electrode sheet is a positive electrode sheet prepared by the preparation method according to any one of claims 8 to 9.